Pengaruh Penerapan Aplikasi Sakti dan Kompetensi SDM terhadap Kualitas Penyajian Data Keuangan LAKIP TA 2023 di RSPAL dr. Ramelan Surabaya - Utomo, Irawan Adji Cahyo; Setiawan, Daniel; Hardiman, Hardiman (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
This research is aimed at determining the impact of the application of reasonable applications and human resources competencies on the quality of presentation of financial data in LAKIP Year 2023 at RSPAL Dr. Ramelan Surabaya. This research uses quantitative methods on populations that include administrative, financial, program, and budget staff, the drafting team, and users of financial reports for LAKIB Year 2023. Simple random sampling technique or stratification of samplings of 39 people. Data collection technique using a Likert scale questionnaire. Data analysis techniques using decryptive statistics and inferential statistics with the help of SPSS software version 27. The results of this study found that the implementation of accurate applications has a positive and significant impact on the quality of presentation of financial data in LAKIP year 2023 of 79.2%. Human resources competence has a positive and significant impact on the quality of presentation of financial data in LAKIP year 2023 by 77.1%. Applying of Sakti application and human resources competence combined have a positive impact and significant influence on the presentation quality of financial information LAKIB year 20–23 by 80.5%. Furthermore, the remaining 19.5% is another variable contribution that the researchers have not observed thoroughly in this research.